Farnesol as a potentiator of antimicrobial photodynamic inactivation on Enterococcus faecalis - Namba, Andressa Mayumi [UNESP]; Santos, Evelyn Luzia de Souza [UNESP]; Garcia, Maíra Terra [UNESP]; Ribeiro, Felipe de Camargo; Figueiredo-Godoi, Lívia Mara Alves [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Junqueira, Juliana Campos [UNESP] (Elsevier, 2022)
Enterococcus faecalis is related to the recurrence of endodontic infections and approaches to intracanal disinfection are necessary. Farnesol, an alcohol commonly found in propolis, has antimicrobial properties, and can enhance the efficacy of some antibiotic therapies. The objective was to evaluate whether farnesol can increase the efficacy of the antimicrobial photodynamic inactivation (aPDI) on E. faecalis, investigating its action on planktonic growth, biofilms, and cell permeability. Planktonic cells and biofilms of E. faecalis were pre-treated with farnesol (0.25 mM) 2 h before aPDI. Methylene blue (1 mg/mL) and laser (660 nm) were employed in the aPDI. As a result, farnesol was able to increase the antimicrobial activity of aPDI in both planktonic and biofilm stages, reaching cell reductions of 4.6 to 6 log10 CFU and 1.3 to 3 log10 CFU, respectively, when compared to aPDI isolated. The efficacy of farnesol in enhancing the anti-biofilm activity of aPDI was also confirmed by electron microscopy, in which a smaller number of bacterial cells and extracellular matrix were verified in the combined therapy compared to aPDI alone. The potentiating action of farnesol was associated with its effects in increasing the cell permeability and methylene blue uptake by the bacterial cells. Therefore, farnesol can be a promising potentiator of aPDI against E. faecalis.
Keywords: Antimicrobial photodynamic inactivation; Biofilms; Enterococcus faecalis; Farnesol